The Effectively Of PAILKEM Learning Strategy In Outdoor Study Method For The Geography Learning Achievement Of The Students In Class XI IPS SMA Negeri 1 Tanete Rilau Barru - Nurlinah, Nurlinah; Zakariah Leo, Muhammad Nur; Badwi, Nasiah (Universitas Negeri Makassar, 2017)
Quasi-experimental research design with pretest-posttest control group design, involving two groups: experimental group was taught learning of strategies PAILKEM in Outdoors Study methods and control groups were taught with conventional learning. This study aims to determine, 1) how the result of students learn geography of the control group, 2) how the results of students learn geography of the experimental group, 3) whether there are differences in geography student learning outcomes between the two groups, 4) whether learning strategies PAILKEM in Outdoor Study methods effective against learning geography results in students XI IPS SMA Negeri 1 Tanete Rilau. Sampling is done with Purposive Sampling. Data collection was carried out through the provision of pre-test and post-test. Data analyzed descriptive and inferential. The results showed that: 1) learning outcome of groups control score average learning outcomes 73.17 and there are 50 percent of the number of learners who achieve the value criterion exhaustiveness, 2) learning outcome of experiment groups average score earned 81.50 93.33 percent and there were a number of learners who achieve the value exhaustiveness minimum criteria or has been completed, 3) there is a significant difference between the results of the study of geography is taught by learning strategies PAILKEM in Outdoor Study method and a control group who were taught with the conventional learning , 4)Â learning strategies PAILKEM in the Outdoor Study method is effective in improving outcomes of learning geography grade XI IPS SMA Negeri 1 Tanete Rilau, Barru Regency